1994
DOI: 10.1063/1.357715
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric devices using semiconductor quantum wells

Abstract: The efficiency of thermoelectric devices are analyzed for a superlattice of semiconductor quantum wells. It is assumed that the quantum wells are the thermoelectric active elements, and the layers between conduct only heat. It is shown that the efficiency of the device depends on the property of both layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…The interface impact of scattering can even cause crossovers in the nanostructure conductivity such that a material with high bulk thermal conductivity is not necessarily the best thermal conductor upon nanostructuring. 21 While thermal-conductivity suppressions can work to improve the efficiency of both thermoelectric and thermoionic cooling, 1, 40,41,42,43,44,45,46 room-temperature estimates, 47 ℓ mfp (T = 300K) ≥ 100 nm, also testifies to some adverse effects even for present devices. Worse, the quest to nanosize modern electronics can only exacerbate the thermal dissipation problems 2,36 since the increase in packing density simultaneously will produce a further degradation in the effective thermaltransport properties.…”
Section: Introductionmentioning
confidence: 99%
“…The interface impact of scattering can even cause crossovers in the nanostructure conductivity such that a material with high bulk thermal conductivity is not necessarily the best thermal conductor upon nanostructuring. 21 While thermal-conductivity suppressions can work to improve the efficiency of both thermoelectric and thermoionic cooling, 1, 40,41,42,43,44,45,46 room-temperature estimates, 47 ℓ mfp (T = 300K) ≥ 100 nm, also testifies to some adverse effects even for present devices. Worse, the quest to nanosize modern electronics can only exacerbate the thermal dissipation problems 2,36 since the increase in packing density simultaneously will produce a further degradation in the effective thermaltransport properties.…”
Section: Introductionmentioning
confidence: 99%
“…The quantum mixing between quantum wells produce a broadening of the lowest subband that changes the density of states from a two-dimensional shape to a three-dimensional one. On the other hand, as was pointed out by Mahan and Lyon, [4] the finite thermal conductivity of the barriers produces a parasitic effect of backflow of heat, without helping the thermoelectric pumping. -4s a result, we found that as we decrease the period of the superlattice, there is a moderate increase in ZT until it reaches a maximum, and a further reduction of the period reduces the figure of merit.…”
mentioning
confidence: 91%
“…Second, several new materials were identified as potential candidates for better thermoelectrics, including the filled skutterudite antimonides [3] and PbTe/Pbl_xEuxTe multiple-quantum-well structures [4]. Among the new materials, superlattices attracted many scientists' attention [5,6,7,8,9]. The interest can be traced back to the quantitative results first obtained by Hicks and Dresselhaus [5] where huge enhancement of thermoelectric properties was predicted for superlattice structures.…”
Section: Introductionmentioning
confidence: 97%